Influence of HIV‐1 V2 sequence variability on bacterial translocation in antiretroviral naïve HIV‐1 infected patients. Issue 12 (11th July 2020) - Balena, Flavia; Bavaro, Davide F.; Volpe, Anna; Lagioia, Antonella; Angarano, Gioacchino; Monno, Laura; Saracino, Annalisa
Abstract: HIV‐1 V2 domain binds α4β7, which assists lymphocyte homing to gut‐associated lymphoid tissue. This triggers bacterial translocation, thus contributing to immune activation. We investigated whether variability of V2 179‐181 binding site could influence plasma levels of lipopolysaccharide (LPS) and soluble cluster of differentiation 14 (sCD14), markers of microbial translocation/immune activation. HIV gp120 sequences from antiretroviral naïve patients were analyzed for V2 tripeptide composition, length, net charge, and potential N‐linked‐glycosylation sites. LPS and sCD14 plasma levels were quantified. Clinical/immuno‐virologic data were retrieved. Overall, 174 subjects were enrolled, 8% with acute infection, 71% harboring a subtype B. LDV 179‐181 was detected in 41% and LDI in 27%. No difference was observed between levels of LPS or sCD14 according to different mimotopes or according to other sequence characteristics. By multivariable analysis, only acute infection was significantly associated with higher sCD14 levels. In conclusion, no association was observed between V2 tripeptide composition and extent of bacterial translocation/immune activation. Highlights: Previous studies suggested an association between 179‐181 V2 tripeptide and the extent of microbial translocation and immune activation. No association was demonstrated between LPS and sCD14 concentrations and the two main variants of V2. No association was found between LPS and sCD14 levels and immunovirological features of our population.